(untitled) (Al-Qamar, 2019)
Tafsir Zia ¢ul Qurān is a Qurānic exegesis (tafsir) written by Pir Muhammad Karam Shah Al-Azhari. It is a great gift for humanity which took two decades for its completion. It is easy to understand as it inculcates the reality and facts in the hearts of readers. This masterpiece of Qurānic exegesis has a great worth in Urdu exploratory literature. If a person is interested in Islamic Theology, can get benifits from it. It contains the glimpse of all masterpieces of Quranic exegesis written in past as well as in modern age. Modern textuality and stylistics are its prominent qualities. All grammatical tactics has been well used in this masterpiece but at the same time, we have the interpretation of thirteen hundred words by using literal, lexical and syntactic researches. We have thought-provoking explanation of Islamic moral philosophy and all other social, economical and political aspects. Tha grammatical tactics used in Tafsir Zia ¢ul Quran might not be found in any other book of Quranic exegesis. One of the best characteristics of Tafsir Zia ¢ul Qurān is that it provides testimony of Qurānic lexicalization from Arabic lexicography. Arabic poetical verses has also been used in this masterpiece to interpret all literal and syntactic researches. Its individuality is that it carries the reflection of its writer’s taste of Arabic poetry as well as his depth of research and meditation. One can’t find this quality anywhere in Urdu exploratory literature except Tafsir Tadabur ul Quran.